Answer: Choice C
h(x) = -x^4 + 2x^3 + 3x^2 + 4x + 5
===========================================
Explanation:
When reflecting the function f(x) over the y axis, we replace every x with -x and simplify like so
f(x) = -x^4 - 2x^3 + 3x^2 - 4x + 5
f(-x) = -(-x)^4 - 2(-x)^3 + 3(-x)^2 - 4(-x) + 5
f(-x) = -x^4 + 2x^3 + 3x^2 + 4x + 5
h(x) = -x^4 + 2x^3 + 3x^2 + 4x + 5
Note the sign changes that occur for the terms that have odd exponents (the terms -2x^3 and -4x become +2x^3 and +4x); while the even exponent terms keep the same sign.
The reason why we replace every x with -x is because of the examples mentioned below
-----------
Examples:
The point (1,2) moves to (-1,2) after a y axis reflection
Similarly, (-5,7) moves to (5,7) after a y axis reflection.
As you can see, the y coordinate stays the same but the x coordinate flips in sign from negative to positive or vice versa. This is the direct reason for the replacement of every x with -x.
2256 fist bumps. 47 fist bumps x 48 friends is 2256 fist bumps.
If you would like to simplify <span>4 + (-3) - 2 * (-6), you can do this using the following steps:
</span><span>4 + (-3) - 2 * (-6) = 4 - 3 + 2 * 6 = 1 + 12 = 13
</span>
The correct result would be 13.
Answer
91
Step-by-step explanation:
62+27+x=180
Answer:
2, 3 and 7,8
Step-by-step explanation: